Synthesis and Characterizations of New Pyrazoles and Study the Toxic Effect of the Compounds in Hella and RD Cancer Cells lines - Fadhil Lafta Faraj (Journal of Global Pharma Technology, 2016)
New Pyrazole Derivatives have been synthesized by reaction of 2-(5-methoxy-3,3-dimethyl-1,3-dihydro-indol-2-ylidene)-malonaldehyde with hydrazine and substituted phenylhydrazine. The chemical purity of the new synthesized compounds was tested by TLC and the chemical structures were characterized by, FT-IR, 1H, and APT 13C NMR. The biological activity of the new synthesized compounds was conducted to investigate the toxic effect of these compounds on the growth of tumor cells represented by the line of HeLa cell line and the human muscle cancer RD in the laboratory. The study included exposure period 24 and 48 hours, and showed good and different results. Keywords: Pyrazole Derivatives, Hydrazine and substituted phenylhydrazine, Hella and RD Cancer Cells lines.